Test–retest reliability and sensitivity of horizontal jump inter-limb asymmetry in youth soccer players across maturity stages - Raouf Hammami; Yassine Negra; Halil Ibrahim Ceylan; Walid Selmi; Ryland Morgans; Francisco Tomás González-Fernández; Nicola Luigi Bragazzi (PLoS ONE, 2026)
The present study examined the test–retest reliability and sensitivity of inter-limb asymmetry derived from the single-leg hop test (SLHT) across different maturity stages in young male soccer players. Sixty-four youth soccer players aged 8–16 years participated in this study and were assessed using the SLHT to quantify inter-limb asymmetry. Participants were divided into prepubertal (n = 34; age: 8.1 ± 1.4 years; body mass: 35.7 ± 3.4 kg; height: 122 ± 9 cm; maturity offset: −2.38 ± 0.83 years) and post-pubertal groups (n = 30; age: 16.5 ± 0.3 years; body mass: 39.6 ± 6.1 kg; height: 154 ± 7 cm; maturity offset: 1.17 ± 0.45 years) according to individual peak height velocity. During the SLHT, participants performed maximal horizontal hops on each leg separately, and the greatest distance achieved was recorded for analysis. Inter-limb asymmetry demonstrated good relative reliability in both groups, with intraclass correlation coefficients of 0.78 and 0.92 for the prepubertal and post-pubertal groups, respectively. Absolute reliability was also acceptable, as the typical error of measurement was < 5% in both groups. Sensitivity analysis showed that the standard error of measurement (SEM) exceeded the smallest worthwhile change (SWC; 0.2 standard deviations) in the prepubertal group, indicating a marginal ability to detect small performance changes. In contrast, the SEM was lower than the SWC in the post-pubertal group, indicating good sensitivity for detecting small changes in performance. These findings indicate that SLHT-derived inter-limb asymmetry scores demonstrate acceptable reliability in youth soccer players across maturity stages, while sensitivity to detect small changes may differ between prepubertal and post-pubertal players. The results contribute to the methodological understanding of inter-limb asymmetry assessment in youth soccer and may assist practitioners and researchers in interpreting asymmetry data across different stages of maturation.